DISTRIBUTION MANAGEMENT SYSTEM PADA PT. MESTIKA ACEH - Irawati; Abdus Salam; Fathurrahmad (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) AMIK Indonesia, 2022)
On the other hand, the system currently running at PT. Mestika Aceh, especially in the goods distribution section, in data processing errors often occur, delays in ordering goods due to stock monitoring which is still done manually with the large number of items available. even if the goods that consumers are looking for are in empty stock, because delays in inputting stock of goods can result in decreased sales, goods that should be able to be sold cannot be sold. The purpose of this research is to design a goods distribution information system at PT. Mustika Aceh. There are two methods that the author uses to collect data, namely Field Studies and Library Studies and for the application development method used is waterfall. From the results of research and observations that have been made at PT. Mestika Aceh, it can be concluded that with the existence of the Goods Distribution Information System Program, the information system at PT. Aceh mustika be precise, and accurate, especially in the distribution of goods. And to obtain information about the distribution of these goods becomes easier and this information system is able to overcome problems that often occur at PT. Mestika Aceh is difficult to control and oversee the distribution of goods and planning the procurement of goods. This information system for procurement of goods can avoid the distribution of excess goods and overcome the scarcity of goods which is certainly highly expected by business actors so that an information system program is created in order to obtain quality information